Efektivitas Kebijakan Perlindungan Anak terhadap Kasus Kekerasan Seksual Studi Tentang Pemenuhan Hak dan Pemulihan Anak Sebagai Korban - Nadaa Nurfazrina Kurniawan Saragih; Asri Vivi Yanti Sinurat; Karina Putri Maharani (Judge : Jurnal Hukum, 2025)
Sexual violence against children constitutes one of the most serious and complex violations of human rights, as it affects not only individual victims but also broader social and economic structures. Child victims of sexual violence face a high risk of experiencing long-term physical, psychological, and social harm, which underscores the state’s obligation to ensure effective and sustainable protection, the fulfillment of children’s rights, and recovery mechanisms. In the Indonesian context, various child protection policies have been formulated, including Law Number 35 of 2014 as an amendment to Law Number 23 of 2002 on Child Protection, which aims to prevent, address, and facilitate the recovery of child victims of sexual violence. Nevertheless, the effectiveness of these policies in practice continues to face significant challenges and therefore requires comprehensive evaluation (Nova and Elda, 2024).This study aims to analyze the effectiveness of child protection policies in addressing cases of sexual violence against children, with a particular focus on the fulfillment of victims’ rights and recovery processes. The study employs a mixed-methods approach by integrating qualitative and quantitative methods. Data were collected through questionnaires, in-depth interviews, and document analysis involving child victims, family members, as well as law enforcement officers and child protection practitioners. The findings indicate that child protection policies are relatively effective in ensuring the fulfillment of basic rights of child victims, such as legal protection and assistance.